2017
DOI: 10.1080/02713683.2017.1285943
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conbercept with Ranibizumab for the Treatment of Macular Edema Secondary to Branch Retinal Vein Occlusion

Abstract: Intravitreal injection of conbercept is shown to be safe and effective for the treatment of ME secondary to BRVO, based on 6-month follow-up data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…; Li et al. ), statistically significant main outcome measures were reported in 29 of 38 (76%) high‐impact publications and in 4 of 7 (57%) of low‐impact publications (p = 0.43). Correspondence between abstract conclusion and significance of main outcome measure was present in 32 of 38 (84%) high‐impact publications and in 6 of 7 (86%) low‐impact publications (p = 0.96).…”
Section: Resultsmentioning
confidence: 87%
“…; Li et al. ), statistically significant main outcome measures were reported in 29 of 38 (76%) high‐impact publications and in 4 of 7 (57%) of low‐impact publications (p = 0.43). Correspondence between abstract conclusion and significance of main outcome measure was present in 32 of 38 (84%) high‐impact publications and in 6 of 7 (86%) low‐impact publications (p = 0.96).…”
Section: Resultsmentioning
confidence: 87%
“…Since the BEAT-ROP trial, intravitreal anti-VEGF for ROP has gained broad popularity in clinics 2 , 12 , 15 , 17 . The present “standard” dosage of IVC for ROP (0.25 mg in 0.025 mL) stands for a origin of adult doseage of Conbercept treated for conditions such as AMD and retinal vein occlusion (0.5 mg in 0.05 mL) 18 , 19 . The dosage used in the treatment of ROP 12 , 0.25 mg, is half the adult dosage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that conbercept is an effective treatment not only for patients with choroidal neovascularization secondary to punctate inner choroidopathy, 21 neovascular AMD, 22 macular edema secondary to branch retinal vein occlusion, 25 but also for patients with PCV. 23 In this retrospective study, treatment-naive PCV patients treated with conbercept using a “3+PRN” method over 6 months of follow-up visits resulted in a significant improvement in visual acuity and anatomical results.…”
Section: Discussionmentioning
confidence: 99%